Analisis Hasil Isolasi DNA dari Bulu Ayam yang Dicuplik dari Pangkal Bulu Muda, Pangkal Bulu Tua dan Ujung Bulu - Alfi Sophian (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: The goal was to provide information on the use of DNA templates in chicken samples so that the molecular research sampling process may employ feathers instead of hurting the test animals. Method: The sample used consisted of 10 Bangkok chickens which were sampled for young feathers and old feathers and the tips of the feathers. Quantitative techniques by comparing the results of DNA isolation which were analyzed using a nano photometer and then confirmed using real-time PCR with the SYBR green method. Result: The analysis of purity and concentration showed that at the base of young chicken feathers, the average value of purity was at 1,790, with an average value of the concentration of 4,210. At the base of the old feather, the average value of purity was 0.638, with an average concentration value that was not detected. Likewise, at the tip of the feather, the average purity value is 0.894 and the concentration value is not detected. Confirmation tests performed on all samples using the real-time PCR melt curve method showed that all samples were detected with a Tm value of 78.5 for young feathers, 78.5 for old feathers, 79.0 for positive controls and 78.7 for positive controls, while negative controls were not detected. Conclusion: DNA isolation can be carried out at the base of the young feathers, the base of the old feathers and the tips of the feathers.